Is Open Lumbar Micro- Discectomy Safe at Periphery of Nepal? - Thapa, Bal K (Nepal Journal of Neuroscience, 2016)
Lumbar disc surgery is performed exclusively for disc herniation. Either low back pain, or sciatica or both are common presentations depending upon the levels of compressed nerve roots. Indications for surgery and MRI needs to be carefully judged upon keeping the economic status of our patients into consideration. Open lumbar (micro) discectomy is safe and successful method for lumbar disc herniations at periphery. Results in these hundred thirteen initial cases with minimum follow up of 5 years indicate that this is not only feasible but safe in these 57 males and 56 female patients aged between 12 and 93. Redo surgeries were not that difficult in this series and were safe. There were 18 cases with Multiple and 95 single levels. Of the single levels it gradually increased as the level gradually decreased in terms of the vertebral counts. L3/4: 3 cases, L4/5: 28 cases and L5/S1 : 64 cases . There were 18 cases of more than one level discs. There were 96 (Micro) discectomies, 11 Laminotomies and 6 Laminectomies. Nepal Journal of Neuroscience 13:30-34, 2016